THE POLICY OF CIVIL SERVANT RECRUITMENT FROM NON-PERMANENT EMPLOYEE - Prayitno, Eko Budi (FIA UB, 2013)
Abstract: The Policy of Civil Servant Recruitment from Non-Permanent Employee. This study is designed to analyze the implementation of Government Regulation Number 48 Year 2005 on the Recruitment of Civil Servants from Non-Permanent Employee in (Temanggung Regency), Indonesia. Research method of this study is the qualitative method. For data collection, the researcher conducted field work and used multiple sources of evidence such as documents, web site, and in depth interview with relevant subjects from BKD of Temanggung. The research results show that Government Regulation Number 48 Year 2005 did not follow Act Number 8 Year 1974 on Public Personnel Principles and Government Regulation Number 98 Year 2000 on the Recruitment of Civil Servant. Lastly, the researcher provides recommendations such as: in terms of recruitment of civil servant, Indonesia Government should apply the principle of good governance and merit. Â Key words: Recruitment of Civil Servant, Non-Permanent Employee, Good Governance, Merit System. Abstrak: Kebijakan Perekrutan Pegawai Negeri Sipil dari Karyawan Tidak Tetap. Studi ini dilakukan untuk menganalisa implementasi Peraturan Pemerintah Nomer 48 Tahun 2005 tentang Pengangkatan Tenaga Honorer Menjadi CPNS (di Kabupaten Temanggung) Indonesia. Metodologi penelitian yang digunakan adalah metode kualitatif. Pengumpulan data bersumber dari dokumen, web site, dan wawancara dengan pejabat (kepala) BKD Kab. Temanggung. Bedasarkan penelitian dapat disimpulkan bahwa PP No. 48 Tahun 2005 kurang selaras dengan UU No. 8 Tahun 1974 tentang Pokok-pokok Kepegawaian dan PP No. 98 Tahun 2000 tentang Pegadaan Pegawai Negeri Sipil. Untuk memperoleh CPNS yang berkualitas maka dalam penerimaan CPNS, pemerintah harus menerapkan prinsip-prinsip good governance dan merit. Â Kata kunci: Pengadaan PNS, Tenaga Honorer, Governance, Merit System.